Molecular investigation of ready-to-eat salads for Giardia duodenalis and Cryptosporidium spp. in Portugal - Clarissa Perez Faria; Adelaide Pereira; Daniela Almeida; Miguel Pinto; Ágata Lourenço; Maria do Céu Sousa (Food and Waterborne Parasitology, 2023)
Foodborne outbreaks are often associated with the consumption of salads. However, published studies on the detection of foodborne pathogens in ready-to-eat salads are scarce. The aim of this study was to detect Giardia duodenalis and Cryptosporidium DNA in ready-to-eat salads, by applying techniques of molecular biology to study the frequency of contamination in salads. A total of 100 packages of ready-to-eat salads containing assorted leafy green vegetables were randomly purchased from hypermarkets located in central regions of Portugal (Coimbra and Viseu). Nested-PCR and qPCR methods were used to detect G. duodenalis and Cryptosporidium DNA. Species and assemblages of the parasites were identified by sequence analysis and PCR. Eighteen of the 100 samples (18%) were positive for G. duodenalis and twelve were sequenced and identified as assemblage A. Cryptosporidium spp. were not detected in any salads. Overall, pre-harvest and post-harvest preventive measures may be need for G. duodenalis control throughout the food production industry, from the field to consumers.